Case Report: Intracranial ectopic schwannoma originating from the internal carotid artery wall - Guo, Zhige; Alafate, Wahafu; Gan, Wu (Frontiers in Surgery, 2025)
This case report presents a rare instance of an ectopic schwannoma originating from the internal carotid artery wall in a 21-year-old male, initially misdiagnosed as an anterior clinoid meningioma. The patient presented with intermittent headaches and dizziness for over two years, aggravated for the past month. Brain MRI revealed a mass above the left side of the parasellar region, hypointense on T1-weighted images and heterogeneously hyperintense on T2-weighted and T2 FLAIR sequences. The operation involved a left frontotemporal craniotomy, and the tumor was found to be compressing and displacing the ipsilateral optic nerve and internal carotid artery. The tumor was completely resected, and postoperative MRI confirmed no residual tissue. Histopathological examination confirmed the diagnosis of schwannoma. This case is unique in its origin from the internal carotid artery wall and its favorable prognosis, with complete functional recovery and resolution of symptoms. The report emphasizes the importance of careful surgical approach and the excellent prognosis of paraclinoid region schwannomas.